Plasmapheresis in the treatment of post-COVID syndrome in dermatology. Case report - Ksenia V. Katkova; Aleksandr S. Chekh; Olga V. Zhukova; Elena V. Denisova; Irina M. Korsunskaya (ZAO "Consilium Medicum", 2024)
The relevance of studying the impact of coronavirus infection on the development and course of autoimmune diseases is due to an increase in the incidence of COVID-19 infection, which is confirmed by reliable data from recent large-scale studies. The trigger mechanisms of autoimmune disorders, particularly those with dermatological manifestations, have been well studied. COVID-19 significantly increases not only the risk of manifestation of autoimmune diseases but also the transformation of a preexisting disorder into severe, atypical, and resistant to standard therapy forms. The article analyzes the data of patients with psoriasis treated in a day hospital from 2021 to 2023 at the affiliate of the Moscow Scientific and Practical Center of Dermatology, Venereology and Cosmetology "V.G. Korolenko Clinic" with exacerbation or onset of the disease reliably associated with a history of coronavirus infection. It is a clinically significant issue since there is a pathomorphosis of a typical pattern of exacerbations: the area of skin lesions increases, exudative and toxicoallergic components are manifested; psoriasis is torpid, which requires the development of individual algorithms for the treatment of patients with psoriasis and post-COVID syndrome, considering the mechanisms of this condition development. An essential aspect in the analysis of this sample of patients was the assessment of general somatic comorbidity, which requires a multidisciplinary approach in selecting therapy to comply with modern criteria for quality treatment, namely its maximum effectiveness and safety.